EFFECT OF SELECTED POLYMERS ON DISSOLUTION AND STABILIZATION OF AMORPHOUS FORM OF MELOXICAM - Obaidat, Rana; Al-taani, Bashar; Al-quraan, Hanan (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: Meloxicam is classified as class II corresponding to its high permeability and low solubility (12Î¼g/ml). This study aims to compare the effect of selected polymers on stabilization of amorphous form, and dissolution of meloxicam by preparation of different solid dispersions using selected polymers (chitosan oligomers, polyvinylpyrrolidone K30, and polyethylene glycols). Methods: These solid dispersions were prepared using two different methods; solvent evaporation method for the two molecular weights chitosan carriers (16 and 11KDa) and polyvinylpyrrolidone-K30 and melting method for the two different molecular weights polyethylene glycol (4000 and 6000). The physicochemical properties of solid dispersions were analyzed using differential scanning calorimetry, Fourier transform infra-red analysis, Powder X-ray diffraction, and scanning electron microscopy. Selected dispersions were then compared to two selected marketed drugs (MobicÂ® and MovenÂ®). Results: Best dissolution rates were obtained for both polyvinylpyrrolidone-K30 and polyethylene glycol 6000, followed by chitosan 16 kDa, chitosan 11 kDa, and polyethylene glycol 4000. Increasing polymeric ratio increased dissolution rate except for chitosan. Precipitation of the drug as amorphous form occurred in chitosan and polyvinylpyrrolidone-K30 dispersions, while no change in crystallinity obtained for polyethylene glycol dispersions. Failure of polyvinylpyrrolidone-K30 in the maintenance of stability during storage time was observed while re-crystallization occurred in chitosan-based dispersions, which ends with preferences to polyethylene glycol dispersions. After comparing the release of selected dispersions with the two selected polymers; all dispersions got a higher release than that of the two marketed drugs release. Conclusion: The dissolution profile of meloxicam has been increased successfully in a reproducible manner.